History of Internet Literary Community “Network Literature” - L. R. Kim (Научный диалог, 2017)
The article covers the history of theoretical views of Internet literary community “Network literature” to their own work. Special attention is paid to literary and critical works on the literature network that were written by members of the community. A review of the parts of theoretical works of the authors of “Network literature” is made. The description of the borders of e-literature is discussed on the basis of the views of “Network literature” authors. The author dwells on analysis of the largest debates of 1997-1998. Attention is paid to the description of the experiments of network authors in the field of multimedia. The question is raised about the reasons for the loss of interest to the “Network literature” by both readers and authors, and a possible solution is proposed. It is shown that the emergence and spread of literary sites with the free publication has had a decisive influence on the way of development of literature in the Internet. The novelty of the research lies in addressing the critical and scientific texts, while the authors of the currently available research publications have analysed the literary works of network authors. The relevance of the study is determined by the increasing importance of Internet literature in the contemporary literary field.